Inventory and distribution of mollusks in the Algerian East coast (El kala region) - Melouah, K; Batah, R.; Zaidi, R. (My University, 2022)
This work aims to study the biodiversity of the mollusks that colonize the mediolittoral stage at the level of the Algerian East coasts (south-west of the Mediterranean) during summer 2021. The qualitative study reveals the existence of nine species: Patella nigra, Patella vulgata, Patella rustica, Patella ulyssiponensis, Patella caerulea, Phorcus lineatus, Mytilus galloprovincialis, Stramonita haemastoma, Acanthopleura granulata. The station 2 (la montagne) has the highest value with a maximum density of 54 ± 9.53 ind/m² while the lowest density has been found in the station 4 (Boufkirine) 9.33 ± 0.57 ind/m². The most important values of index of the diversity and evenness index (E) were recorded in station 2 (H'=2.16; E=0.77) respectively. The leading mollusk in the studied area is the patelidae Patella rustica (74.83%) followed by the gastropod Stramonita haemastoma (26.57%) and the bivalve Mytilus galloprovincialis (23.78%).